Fabrication of Millimeter‐Long Carbon Tubular Nanostructures Using the Self‐Rolling Process Inherent in Elastic Protein Layers. Issue 31 (19th June 2017) - Ko, Hyojin; Deravi, Leila F.; Park, Sung‐Jin; Jang, Jingon; Lee, Takhee; Kang, Cheong; Lee, Jin Seok; Parker, Kevin Kit; Shin, Kwanwoo
Abstract : Millimeter‐long conducting fibers can be fabricated from carbon nanomaterials via a simple method involving the release of a prestrained protein layer. This study shows how a self‐rolling process initiated by polymerization of a micropatterned layer of fibronectin (FN) results in the production of carbon nanomaterial‐based microtubular fibers. The process begins with deposition of carbon nanotube (CNT) or graphene oxide (GO) particles on the FN layer. Before polymerization, particles are discrete and nonconducting, but after polymerization the carbon materials become entangled to form an interconnected conducting network clad by FN. Selective removal of FN using high‐temperature combustion yields freestanding CNT or reduced GO microtubular fibers. The properties of these fibers are characterized using atomic force microscopy and Raman spectroscopy. The data suggest that this method may provide a ready route to rapid design and fabrication of aligned biohybrid nanomaterials potentially useful for future electronic applications. Abstract : Millimeter‐long conducting fibers can be fabricated from carbon nanomaterials via a simple method involving the release of a prestrained protein layer. Before the self‐rolling process, nanoparticles are discrete, but after self‐rolling process the nanoparticles become entangled to form an interconnected network clad. Selective removal of the protein layer yields a long freestanding, conducted carbon nanotube or graphene oxide microtubular fiber.